Cavity dynamics in 10 wt% gelatin penetration of rifle bullet. (December 2018) - Liu, Susu; Xu, Cheng; Wen, Yaoke; Wang, Shu; Zhou, Jingling; Zhou, Xinkai
Highlights: Cavity dynamics in gelatin was studied. A motion model of temporary cavity is established in gelatin penetrations of rifle bullets. The motion model is well consistent with the penetration tests. The radial movement of cavity is characterized by the behavior of bullet and the characteristic velocity. Abstract: In wound ballistics, modeling the penetration-cavitation dynamics will set the basis for evaluating the damaging efficiency of projectiles. In our previous study, a motion model to characterize the behavior of rifle bullets has been established and verified in the gelatin penetration. In order to reveal the cavity production analytically, in combination with parameters obtained from the motion model of rifle bullet, cavity dynamics in gelatin was studied and a motion model of temporary cavity in gelatin penetrations of rifle bullets was proposed and verified by comparison with experimental results in terms of maximum cavity wall radius, radial movement along the penetration trajectory and temporary cavity profiles. It can be concluded that calculated results of the cavity motion model agree well with experiment data for penetration of 7.62 mm and 5.56 mm rifle bullets. And the radial movement of cavity can be characterized by the behavior of bullet and the characteristic velocity. It is significant for the trauma assessment to develop an appropriate cavitation model in gelatin for penetrations of rifle bullet.